DEVELOPING ESP TEACHER’S HANDBOOK TO TEACH SPEAKING FOR NURSING - Izzah Fijriyah (Abjadia, 2016)
This study was conducted to develop a guideline called ESP teacher’s handbook to teach Speaking II for the Nursing Department students which are appropriate with the students’ needs and current ESP syllabus in University of Muhammadiyah Malang (UMM). The development of the product was because the result of the preliminary study showed that the Nursing Department students in UMM have lack of intention and confidence to participate actively in the classroom due to some materials that cannot interestingly trigger students’ motivations. The cooperative learning and communication practice was emphasized in developing the product. It can be said that through the try-out and experts’ validation, this teacher’s handbook has fulfilled the challenge for producing an edutainment of teaching materials that can solve the problems and meet the needs mentioned in the background of the research. وقد أجريت هذه الدراسة لتطوير الكتاب التوجيهي للمعلم الذي سمي بـ ESP  لتدريس مهارة الكلام الثاني لقسم التمريض، وهو الكتاب المناسب باحتياجات الطلاب وبالمناهج ESP في جامعة محمدية مالانج  (UMM). وإن تطوير هذا المنتج بسب ما ظهر من الطلاب قسم التمريض في قسم بجامعة محمدية مالانج  (UMM) الذين لا يملكون الحماسة والنشاط عند مشاركة الفصول الدراسية، وذلك لأن بعض المواد لا يمكن أن تؤدي المثير ولا تدفعهم إلى التعلم بفعال. وقد تم التأكيد على ممارسة التعلم والاتصالات التعاونية في تطوير المنتج. ويمكن القول أنه من خلال محاولة التدريجي والتحقق من صحة الخبراء، قد وصل هذا المنتج درجة الصحة في المحتويات واللغة ووصف المواد والمناسبة بالمنهج الدراسي. وقد يمكن هذا المنتج أن يحل المشاكل وتلبية الاحتياجات المذكورة في الخلفية للبحث.